2021
DOI: 10.3389/fendo.2021.716533
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dysmetabolic Sarcopenia Among Insulin Sensitive Tissues: A Narrative Review

Abstract: Sarcopenia is a common muscular affection among elderly individuals. More recently, it has been recognized as the skeletal muscle (SM) expression of the metabolic syndrome. The prevalence of sarcopenia is increasing along with visceral obesity, to which it is tightly associated. Nonetheless, it is a still underreported entity by clinicians, despite the worsening in disease burden and reduced patient quality of life. Recognition of sarcopenia is clinically challenging, and variability in study populations and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…Sarcopenic (loss of muscle mass, often associated with ageing) obesity is the concept that an individual can be meet clinical definitions of obesity (BMI > 30 kg/m 2 ) and simultaneously exhibit skeletal muscle wasting [ 68 , 69 ]. Sarcopenic skeletal muscles are known to be insulin resistant even in the setting of low whole-body fat stores [ 70 ], and considering that skeletal muscle is a primary site of both insulin action and glucose uptake/storage [ 71–75 ], sarcopenia contributes significantly to systemic metabolic syndrome [ 76 ]. Numerous studies have shown detrimental epidemiological consequences of sarcopenic obesity on cancer incidence, progression, and survival, with the largest influence on cancer incidence [ 53 , 54 , 69 , 77–81 ].…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%
“…Sarcopenic (loss of muscle mass, often associated with ageing) obesity is the concept that an individual can be meet clinical definitions of obesity (BMI > 30 kg/m 2 ) and simultaneously exhibit skeletal muscle wasting [ 68 , 69 ]. Sarcopenic skeletal muscles are known to be insulin resistant even in the setting of low whole-body fat stores [ 70 ], and considering that skeletal muscle is a primary site of both insulin action and glucose uptake/storage [ 71–75 ], sarcopenia contributes significantly to systemic metabolic syndrome [ 76 ]. Numerous studies have shown detrimental epidemiological consequences of sarcopenic obesity on cancer incidence, progression, and survival, with the largest influence on cancer incidence [ 53 , 54 , 69 , 77–81 ].…”
Section: Obesity's Link To Insulin Resistance and Hyperinsulinemiamentioning
confidence: 99%
“…Although the origin of sarcopenia is multifactorial, ranging from aging and cancer-related mechanisms, the role of chronic systemic inflammation is associated with the onset of skeletal muscle alterations. Its role in the context of metabolic syndrome requires additional considerations as impaired insulin activity in skeletal muscle is responsible for the altered molecular pathways and clinical manifestations of sarcopenia [ 21 ].Weight loss is a critical factor to reduce inflammation, and the effect can be related to body fat loss [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathological mechanisms remain to be unravelled fully, but circulating nutrient excess and pro-inflammatory cytokines are widely recognised risk factors for muscle [ 5 ] and beta cell [ 6 ] dysfunction. Insulin resistance also manifests itself during loss of skeletal muscle function and mass (sarcopenia – [ 7 ]) that is associated with ageing [ 8 ] and chronic medical disorders such as advanced liver disease [ 9 ] and chronic kidney disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%